2015
DOI: 10.5937/pramed1501067v
|View full text |Cite
|
Sign up to set email alerts
|

The descriptive and epidemiological characteristics of cervical cancer

Abstract: Karcinom grlića materice je ozbiljan javno zdravstveni problem kako u svetu tako i kod nas. Kontrola karcinoma grlića materice pored prevencije podrazumeva ranu dijagnostiku i lečenje, ali i preciznu registraciju i praćenje obolelih žena. Da bi bila obezbeđena dobra kontrola bolesti, svi ovi delovi sistema moraju funkcionisati paralelno. Cilj rada je sagledavanje osnovnih deskriptivno-epidemioloških karakteristika obolelih i umrlih žena od raka grlića materice u svetu, Evropi i Srbiji. Poseban osvrt i detaljan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…Therefore, there is no justification for the fact that over seven hundred women die from this disease in the world every day. Numerous studies in this area have shown the same results, that women of higher socioeconomic status measured by education, financial status, and economic status have achieved greater coverage with this preventive examination [21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there is no justification for the fact that over seven hundred women die from this disease in the world every day. Numerous studies in this area have shown the same results, that women of higher socioeconomic status measured by education, financial status, and economic status have achieved greater coverage with this preventive examination [21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%